Ultra-processed food consumption and increased risk of metabolic syndrome: a systematic review and meta-analysis of observational studies - Shu, Long; Zhang, Xiaoyan; Zhou, Jianying; Zhu, Qin; Si, Caijuan (Frontiers in Nutrition, 2023)
Background:Although higher consumption of ultra-processed food(UPF) has been linked to a higher risk of metabolic syndrome(MetS), the results remain controversial. Herein, we performed a systematic review and meta-analysis of observational studies to clarify the relationship between UPF consumption defined by the NOVA framework and risk of MetS. Methods: An extensive literature search on PubMed, ISI Web of Science, EBSCO and China National Knowledge Infrastructure (CNKI) databases was conducted to search for the relevant articles published priori to January 2023, and newly published articles between January 2023 and March 2023 were re-searched. Random-effects or fixed-effects models were adopted to calculate the pooled relative risks(RRs) and 95% confidence intervals(CIs).The between-study heterogeneity was explored using the Cochran’s Q test and I-square(I2). Publication bias was investigated using the visual inspection of asymmetry in funnel plots and Begg’s and Egger’s tests. Results: Nine studies(six cross-sectional and three prospective cohort studies) totaling 23500 participants with 6192 MetS cases were included in the final analysis. The pooled effect size for the highest versus lowest categories of UPF consumption indicated a positive association with the risk of MetS(RR:1.25, 95%CI: 1.09-1.42, P<0.0001). Subgroup analyses revealed a positive association between consumption of UPF and MetS risk in cross-sectional studies(RR:1.47, 95%CI: 1.16-1.87, P=0.002), and no significant association in cohort studies(RR:1.10, 95%CI: 0.96-1.27, P=0.104), respectively. In addition, a more significant association between UPF consumption and increased risk of MetS was found in the subgroups of study quality<7(RR:2.22; 95%CI:1.28-3.84, P=0.004) than study quality≥7(RR:1.20; 95%CI: 1.06-1.36, P=0.005). Similarly, when we performed analyses separately by sample size, there was a significant association between UPF consumption and MetS risk in sample size≥5000(RR:1.19; 95%CI: 1.11-1.27, P<0.0001), and in sample size<5000(RR:1.43; 95%CI: 1.08-1.90, P=0.013), respectively. Conclusions: Our findings suggest that higher consumption of UPF is significantly associated with an increased risk of MetS. Further longitudinal studies are needed to confirm the effect of UPF consumption on MetS.